Evaluasi Program Perbaikan Gizi Masyarakat Kategori Balita Berstatus Stunting Di Kecamatan Sungai Pandan Kabupaten Hulu Sungai Utara (Studi Program Gerakan Atasi Stunting Dengan ASI “GUSI”) - Puteri Anggraini Oktavianty; Reno Affrian; Bambang Kusbandrijo; Achluddin Ibnu Rochim (Jurnal Niara, 2023)
Nutritional problems, especially about stunting, are a national problem, not least in Hulu Sungai Utara Regency. Based on data from the Alabio Inpatient Health Center UPT, the number of stunting toddlers in Sungai Pandan District in 2020 was 118 toddlers and in 2021 there were 121 toddlers. This study aims to (1) describe and analyze the evaluation of the community nutrition improvement program for the toddler category with stunting status, the study program for overcoming stunting with breastfeeding (GUSI) and (2) describe and analyze the supporting and inhibiting factors for the community nutrition improvement program for the stunting status category of toddlers in the sub-district Pandan River, Hulu Sungai Utara Regency. The research method used in this study is a descriptive method with a qualitative approach. Determination of informants purposively (aimed at), the analytical techniques used are data condensation, data display and verification. The results of the study showed that (1) the program for improving community nutrition in the category of toddlers with stunting status in the innovation of the movement to overcome stunting with breastfeeding (GUSI) has not run optimally, seen from the mother's awareness of nutritional intake and understanding of exclusive breastfeeding which is still low, (2) Factors supporters, 1. Competence of Human Resources (HR), (3) Inhibiting factors, 1. Economics, 2 Parenting patterns. Suggestions for improving community empowerment programs and improving inter-institutional coordination